Agricultural co-operative sustainability: Evidence from four Chinese pig production co-operatives. (1st October 2018) - Ji, Chen; Jia, Fu; Xu, Xuchu
Abstract: The aim of the study is to explore how agricultural co-operatives achieve sustainability in an uncertain environment. To do this, an in-depth ethnographical case study was carried out, including interviews with co-operative managers, members and stakeholders of four pig production co-operatives in China; observations during field visits; and collection of archival data. We found that a co-operative's resilience and dynamic capabilities individually are necessary for co-operative sustainability. They jointly represent sufficient and necessary conditions for co-operative sustainability and determine three types of co-operatives: "Star", "Question Mark" and "Dog". This research contributes to sustainability research by extending it to a special form of organization, i.e., agricultural co-operatives, which are different from investor-owned firms, operationalizing co-operative resilience, dynamic capabilities and sustainability and proposing causal relationships between them. Highlights: Co-operative's resilience and dynamic capabilities individually are necessary condition for co-operative sustainability. Co-operative's resilience and dynamic capabilities are both sufficient and necessary towards co-operative sustainability. Co-operative's resilience and dynamic capabilities determine three types of co-operatives.